Implications of overlooked drivers in Ethiopia's urbanization: curbing the curse of spontaneous urban development for future emerging towns. Issue 10 (October 2022) - Benti, Solomon; Terefe, Heyaw; Callo-Concha, Daniel
Abstract: In Ethiopia, urban areas are defined basically as places having a minimum population of 2, 000. The current coverage of urban areas in the country is less than 20%, and even the majorities are small towns that account more than 85% of the urbanized areas in the country. However, urbanization in the country is increasing rapidly, at a rate of 4.63% annually. Spatially, the highest urbanization ratios occur in small towns surrounding the Ethiopia's capital city, Addis Ababa. Still, the recently urbanized areas are characterized as shanty, slum and spontaneous. On the other hand, the current rate of urbanization in the country indicates that there will be more urbanized areas in the future, which need better urban planning and management. Therefore, the purpose of this research was to identify the key drivers of the development of Ethiopia's urbanization, and to identify the management gaps that could help to predict future urbanization hotspots and trends from their early stages. Methodologically, both primary and secondary data sources were systematically applied: current urban planning and related documents, as well as land-use plans, and furthermore, high resolution historical satellite imageries of 2005, 2008 and 2018 from Google Earth Pro were analyzed. Complementary, and for validation purposes interviews and focus group discussions with experts were carried out between 2018–2021, together with on-site investigation. The results show that the drivers for the emergence of spontaneous urban development in Ethiopia relate primarily to socio-cultural components, such as in the case of worshiping places, local markets, educational and administrative centers. Physical infrastructure, such as roads played also a significant but subordinate role in the intensification of such developments. Our results demonstrate how an ineffective management of these factors has contributed to a dysfunctional urban growth. Finally, a green field level proactive planning approach is proposed and commented. Abstract : Haphazard urbanization; Land-cover changes; Planning approach; Sebeta; Spatial drivers; Spontaneous development.